The Pragmatics of Stereotypes in Trevor Noah’s Stand-up Comedy Routines - Idania Rosa Castro Bravo (Estudios de Lingüística)
This paper addresses the intricate task of studying humor considering its dependence on cognition, emotions and even human perception. It focuses on the use of stereotypes within verbal humor, having stand-up comedy as the center of the study. Specifically, it examines how Trevor Noah, a South African comedian, utilizes stereotypes to entertain and produce a comic effect in his stand-up comedy. To carry out this study, we used and analyzed a real corpus based on 11 television-mediated stand-up comedy shows. These routines were performed by Noah between 2009 and 2022. Consequently, the study has been based on a mixed methodology, considering the qualitative and quantitative paradigms for its completion. The quantitative paradigm, particular to corpus linguistics, served to quantify the number of occurrences of the different stereotypes in the TREVOR-UP corpus, whereas the qualitative paradigm helped in describing and analyzing the sequences containing stereotypical views in detail. The study and examination of stereotypes showed that 90.3% of the sequences of TREVOR-UP corpus contained a stereotypical reference being the cultural stereotypical views, the most recurrent in the corpus. In addition, the use of race/ethnicity, political, and language stereotypes are frequent and follow the cultural stereotypical views in aiding the construct of Trevor Noah’s humorous discourse. The use of the different stereotypical categories was directly connected to the use of a significant amount of the different rhetorical-pragmatic strategies described, focusing on mitigation and direct speech. Lastly, the application of the Intersecting Circles Model (ICM) of humorous communication proposed by Francisco Yus in 2013, evidenced that the collective cultural assumptions based on stereotypical instances which in turn, activates the cultural frame, is a common practice by the comedian when performing. Accordingly, this showed that the use of the makesense frame + cultural frame in ICM altogether, is employed to manipulate and predict the audience’s response to the comedian’s particular humorous discourse.